Part geometry-driven crystallographic texture control in a 3D-printed austenitic steel – a strategy for near-monocrystalline microstructure generation - Chandra, Shubham (2023)
We propose and employ a novel X-shaped geometry to strengthen the 〈001〉 || z crystallographic texture – distinctive of the electron beam powder-bed fusion technique, for a 3D-printed austenitic stainless steel of type 316 L. The prism angles of the X-shaped parts are varied among 60, 90, and 120 degrees (X-60, X-90, and X-120) to investigate the effect it has on the parts’ properties. Strikingly, the strength of the 〈001〉 || z crystallographic texture and columnar grain width with increasing prism angle is seen to follow a ‘bell-curve’ profile which peaks with the X-90 shape. A distinct mechanical response of X-shaped samples is obtained with X-60 samples showing significantly stronger strain-hardening behavior along with cracking concentrated along the grain boundaries between 〈110〉 || z and 〈001〉 || z grains. Molecular dynamics simulations are utilized to rationalize this phenomenon.